Manfaat Penerapan Audit Sumber Daya Manusia Pada Perusahaan - Sangkala, Masnawaty (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this article is to look at the effectiveness of employee performance in implementing human resource audits in companies. This article is a qualitative descriptive article using interview and questionnaire data collection methods for the human resource management division. The data analysis method used is qualitative analysis by performing the function of assessing personnel effectiveness based on comparisons between criteria, cause and effect. Based on the research that has been done, it is known that the activities of the human resource function in companies have been running effectively in implementing human resource audits.